CRISPR/Cas9 genome‐editing applied to MdPGT1 in apple results in reduced foliar phloridzin without impacting plant growth. (5th December 2022) - Miranda, Simón; Piazza, Stefano; Nuzzo, Floriana; Li, Mingai; Lagrèze, Jorge; Mithöfer, Axel; Cestaro, Alessandro; Tarkowska, Danuše; Espley, Richard; Dare, Andrew; Malnoy, Mickael; Martens, Stefan
SUMMARY: Phloridzin is the most abundant polyphenolic compound in apple ( Malus  ×  domestica Borkh.), which results from the action of a key phloretin‐specific UDP‐2′‐ O ‐glucosyltransferase (MdPGT1). Here, we simultaneously assessed the effects of targeting MdPGT1 by conventional transgenesis and clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 (Cas9)‐mediated genome editing. To this end, we conducted transcriptomic and metabolic analyses of MdPGT1 RNA interference knockdown and genome‐edited lines. Knockdown lines exhibited characteristic impairment of plant growth and leaf morphology, whereas genome‐edited lines exhibited normal growth despite reduced foliar phloridzin. RNA‐sequencing analysis identified a common core of regulated genes, involved in phenylpropanoid and flavonoid pathways. However, we identified genes and processes differentially modulated in stunted and genome‐edited lines, including key transcription factors and genes involved in phytohormone signalling. Therefore, we conducted a phytohormone profiling to obtain insight into their role in the phenotypes observed. We found that salicylic and jasmonic acid were increased in dwarf lines, whereas auxin and ABA showed no correlation with the growth phenotype. Furthermore, bioactive brassinosteroids were commonly up‐regulated, whereas gibberellin GA4 was distinctively altered, showing a sharp decrease in RNA interference knockdown lines. Expression analysis by reverse transcriptase‐quantitative polymerase chain reaction expression analysis further confirmed transcriptional regulation of key factors involved in brassinosteroid and gibberellin interaction. These findings suggest that a differential modulation of phytohormones may be involved in the contrasting effects on growth following phloridzin reduction. The present study also illustrates how CRISPR/Cas9 genome editing can be applied to dissect the contribution of genes involved in phloridzin biosynthesis in apple. Significance Statement: We applied RNA interference silencing and CRISPR/Cas9‐mediated genome editing to target the key gene MdPGT1 involved in the synthesis of phloridzin, an abundant secondary metabolite naturally occurring in apple. Both approaches caused a reduction in phloridzin but led to contrasting growth phenotypes, along with differential phytohormone profiles following MdPGT1 alteration. The present study provides insight into the key role of brassinosteroids and gibberellins on the effects mediated by MdPGT1 .